Health Information Technology Documentation and Referrals for Intimate Partner Violence and Sexual Assault - Richardson, Joshua E.; Houston-Kolnik, Jaclyn; Ramos, Stefany; Oxner, Devin; Presler-Jur, Paige (Applied Clinical Informatics, 2024)
Background Hospital settings provide a unique opportunity to screen for intimate partner violence (IPV) and sexual assault (SA) yet often lack health information technology (IT) solutions for generating reliable and valid medicolegal documentation via forensic reports.Objectives The objective of the project was to evaluate a pilot, technology “tool” for documenting cases of IPV and SA that could support forensic nurse examiners and related stakeholders in generating high-quality documentation and coordinating victim support services.Methods The tool was a digital health intervention implemented for use among forensic nurse examiners, law enforcement, victim support organizations, and more within four counties of California. We conducted a mixed-methods pilot study that captured data around the adoption, use, and impact of having access to the newly implemented tool.Results The tool successfully went live in all four pilot counties at different time points with different proportions of use by county and form type: exams, referrals, addenda, risk assessments, and other. Participants were motivated to use the tool out of a perceived need for data handling functionalities that went beyond traditional manual (paper) means. Key functionalities included body mapping, data quality controls within validated forms, attaching addenda to already existing case reports, and the means to distribute data to external recipients. Further study and development are needed on functions to incorporate into body maps and forms and understanding the information needs of law enforcement and victim support organizations.Conclusion Our evaluation demonstrated the feasibility and acceptability of a health IT tool to support forensic nurse documentation of IPV and SA and direct information to multiple legal and support-related stakeholders. Areas of future development include integrating IPV- and SA-related data standards for digitized forms, enhancements to the body mapping feature, and understanding the needs of those who receive digital data from forensic nurse examiners within the tool.
Keywords: medical informatics; forensic nursing; intimate partner violence